Nusyuz Menurut Pemikiran Sayyid Qutb dalam Tafsir Fi Zilalil Qur’an - Qadri, Busran; Murdiana, Elfa; Bustomi, Ahmad (Tapis: Jurnal Penelitian Ilmiah, 2022)
Nusyuz has always been related to the wife's non-compliance with her husband. Therefore, there is a difference in resolving nusyuz cases committed by husbands and wives. If nusyuz is performed by the wife, then the husband has the right to advise the wife, separate the bed, and hit with a note of not hurting. Whereas, when nusyuz is done by the husband, there is a tendency for the wife to should give up some of her rights in order to carry out a peace agreement. The purpose of this study is to enlighten the reader regarding how the concept of nusyuz is based on Sayyid Qutb’s thoughts. Kind of this study is library research, employing normative and sociological approaches. The purpose of this study is to understand Sayyid Qutb's understanding of nusyuz concept. The data in this research is taken from a tafsir book written by Sayyid Qutb entitled Tafsir Fi Zilalil Qur’an, books, and scientific research relevant to nusyuz. Afterward, in analyzing data, the researcher uses the theory formula explained by M. Quraish Shihab about the Qur’an interpreted method. This study explained that nusyuz is an act in which a person (husband or wife) accentuates and elevates by disobeying, and who does not do their obligation as a husband or wife and its solutions depend on his/her position in the household, education, family, and country's condition.